2011
DOI: 10.1021/es202793c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Local Mercury Deposition from a Coal-Fired Power Plant Using Mercury Isotopes

Abstract: Coal combustion accounts for approximately two-thirds of global anthropogenic mercury (Hg) emissions. Enhanced deposition of Hg can occur close to coal-fired utility boilers (CFUBs), but it is difficult to link specific point sources with local deposition. Measurement of Hg stable isotope ratios in precipitation holds promise as a tool to assist in the identification of local Hg deposition related to anthropogenic emissions. We collected daily event precipitation samples in close proximity to a large CFUB in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
171
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(191 citation statements)
references
References 58 publications
(155 reference statements)
17
171
2
Order By: Relevance
“…Further experimental and observational work on Hg isotope MDF during coal combustion, metal refining and liquid Hg 0 use is needed to confirm the presented conceptual models. High-precision Hg isotope measurement of total gaseous Hg (TGM, GEM+GOM) and precipitation Hg has been reported for several N-American and European regions (Chen et al, 2012;Demers et al, 2013Demers et al, , 2015Donovan et al, 2013;Fu et al, 2014;Gratz et al, 2010;Sherman et al, 2010Sherman et al, , 2012Sherman et al, , 2015Wang et al, 2015). Global TGM is enriched in the heavy isotopes (d 202 Hg=0.51 ± 0.41 ‰, 1SD) (Demers et al, 2013(Demers et al, , 2015Fu et al, 2014;Gratz et al, 2010;Sherman et al, 2010) compared to our model estimated GEM emissions (Table 1).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Further experimental and observational work on Hg isotope MDF during coal combustion, metal refining and liquid Hg 0 use is needed to confirm the presented conceptual models. High-precision Hg isotope measurement of total gaseous Hg (TGM, GEM+GOM) and precipitation Hg has been reported for several N-American and European regions (Chen et al, 2012;Demers et al, 2013Demers et al, , 2015Donovan et al, 2013;Fu et al, 2014;Gratz et al, 2010;Sherman et al, 2010Sherman et al, , 2012Sherman et al, , 2015Wang et al, 2015). Global TGM is enriched in the heavy isotopes (d 202 Hg=0.51 ± 0.41 ‰, 1SD) (Demers et al, 2013(Demers et al, , 2015Fu et al, 2014;Gratz et al, 2010;Sherman et al, 2010) compared to our model estimated GEM emissions (Table 1).…”
Section: Discussionmentioning
confidence: 54%
“…During the thermal processing of source materials, Hg in source materials is transformed into GEM, GOM and PBM in generated flue gases by a series of physicochemical reactions (oxidation, reduction, adsorption, diffusion etc.). These phase and redox transformations of Hg in high-temperature facilities are expected to induce significant Hg isotope MDF, but no photochemical MIF (Sherman et al, 2012;Sonke et al, 2010;Sun et al, 2013; (Biswas et al, 2008;Lefticariu et al, 2011;Sherman et al, 2012;Sun et al, 2013Sun et al, , 2014aSun et al, , 2014bYin et al, 2014a). In contrast, only a limited number of oil sand samples from Athabasca, Canada have been reported .…”
Section: Methods Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hg isotopes can undergo mixing and fractionation by two types of pathways that impart distinct Hg isotopic compositions on natural environmental samples. Studies have shown distinct Hg isotopic compositions in samples those impacted by coal-fired power plants, metal refineries, and gold amalgamation [110][111][112]. Significant fractionations of Hg isotopes have been observed during AMDEs [88] and in-plume reduction [113] as well as in background atmospheric conditions via photochemical reduction, oxidation, and sorption to particles [114•].…”
Section: Resultsmentioning
confidence: 99%
“…202 Hg and D 199 Hg values have been reported in environmentally relevant matrices such as rocks (Smith et al, 2008), mineral deposits (Hintelmann and Lu, 2003;Smith et al, 2005Smith et al, , 2008Stetson et al, 2009;Sonke et al, 2010), coals (Biswas et al, 2008;Lefticariu et al, 2011;Sun et al, 2014;Yin et al, 2014b), soils (Biswas et al, 2008;Zhang et al, 2013;Feng et al, 2013), sediments (Gehrke et al, 2011;Foucher and Hintelmann, 2009;Feng et al, 2010;Liu et al, 2011;Bartov et al, 2013;Donovan et al, 2013;Ma et al, 2013;Yin et al, 2013aYin et al, , 2015, water (Štrok et al, 2014), air (Demers et al, 2013;Rolison et al, 2013), precipitation (Gratz et al, 2010;Chen et al, 2012;Demers et al, 2013;Sherman et al, 2011Sherman et al, , 2015 and biological samples Blum et al, 2013;Demers et al, 2013;Yin et al, 2013b). With well-defined source signatures, researchers may estimate the relative contribution of sources of Hg through the utilization of binary and/or triple mixing models (Foucher and Hintelmann, 2009;Feng et al, 2010;Liu et al, 2011;Bartov et al, 2013;Donovan et al, 2013;Ma et al, 2013;…”
mentioning
confidence: 99%